Emerging Targets for Developing T Cell-Mediated Vaccines for Human Immunodeficiency Virus (HIV)-1 - Wijesundara, Danushka K.; Ranasinghe, Charani; Grubor-Bauk, Branka; Gowans, Eric J. (Frontiers in Microbiology, 2017)
Human immunodeficiency virus (HIV)-1 has infected >75 million individuals globally, and, according to the UN, is responsible for ~2.1 million new infections and 1.1 million deaths each year. Currently, there are ~37 million individuals with HIV infection and the epidemic has already resulted in 35 million deaths. Despite the advances of anti-retroviral therapy (ART), a cost-effective vaccine remains the best long-term solution to end the HIV-1 epidemic especially given that the vast majority of infected individuals live in poor socio-economic regions of the world such as Sub-Saharan Africa which limits their accessibility to ART. The modest efficacy of the RV144 Thai trial provides hope that a vaccine for HIV-1 is possible, but as markers for sterilizing immunity are unknown, the design of an effective vaccine is empirical, although broadly cross-reactive neutralizing antibodies (bNAb) that can neutralize various quasispecies of HIV-1 are considered crucial. Since HIV-1 transmission often occurs at the genito-rectal mucosa and is cell-associated, there is a need to develop vaccines that can elicit CD8+ T cell immunity with the capacity to kill virus infected cells at the genito-rectal mucosa and the gut. Here we discuss the recent progress made in developing T cell-mediated vaccines for HIV-1 and emphasize the need to elicit mucosal tissue-resident memory CD8+ T (CD8+ Trm) cells. CD8+ Trm cells will likely form a robust front-line defense against HIV-1 and eliminate transmitter/founder virus-infected cells which are responsible for propagating HIV-1 infections following transmission in vast majority of cases.